Essentials of foreign exchange trading - Chen, James (Hoboken, N.J. : Wiley, 2009)
This indispensable guide features easy to use, at-your-fingertips information on trading in the forex market. Its nuts and bolts presentation offers straightforward advice on: whether forex trading is right for you, the mechanics of forec trading, the tools for trading forex- from technical analysis to fundamental analysis to specific trading strategies, which factors drive currency exchange rate movement, essential elements of successful forex trading, and how top currency traders tackel the markets on a daily basis.
Includes index.
rpm 26/06/14
Loans
Keywords: Foreign exchange market; Foreign exchange futures; Investments